Screening of Actinomycetes Producing Antibacterial Substances and Indole Acetic Acid IAA and Optimization of Growth and IAA Production Conditions in Streptomyces sp SF5 - Ameur, Hanane (International Journal of Pharmaceutical & Biological Archive, 2012)
Screening of Actinomycetes Producing Antibacterial Substances and Indole Acetic Acid IAA and Optimization of Growth and IAA Production Conditions in Streptomyces sp SF5